2018
DOI: 10.1021/acs.jpcc.8b00157
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Ultraviolet Ionization-Induced Reaction of Neutral Au2Al2O3 Clusters with Methane

Abstract: Identification of molecular-level mechanisms of methane activation is very important in order to transform the most stable alkane molecule into valueadded chemicals. Herein, by employing a homemade time-of-flight mass spectrometer coupled with a vacuum ultraviolet (VUV) laser system, the reactions of neutral heteronuclear metal oxide clusters Au x Al y O z (x = 1, 2) with CH 4 have been investigated. The interesting channel of Au 2 Al 2 O 3 H + production was observed for the interaction of a Au 2 Al 2 O 3 clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 75 publications
0
5
0
Order By: Relevance
“…[23][24][25][26][27] By conducting investigations of metal cluster catalysis, extensive efforts have been made to improve the reaction activity, and it is recognized that the specific sizes and geometric/electronic structures of clusters are often crucial factors in determining the resulting mechanisms and reaction rates. [28][29][30][31][32][33] Also, the binding energies can fluctuate with increasing numbers of atoms, allowing clusters at a certain size to transform from a two-dimensional planar structure to a three-dimensional (3-D) structure (e.g., Pt 3 vs Pt 4 ), and occasionally leading to "magic" number species such as Al 13 − , Ag 13 − , and 12,[34][35][36] In many studies, clusters are supported on a selected substrate in order to evaluate the catalytic reactions in a practical way. The interaction between the metal clusters and support is a fundamental characteristic in heterogeneous catalysis and plays an essential role in elucidating the electronic structures, adsorption behavior, and catalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27] By conducting investigations of metal cluster catalysis, extensive efforts have been made to improve the reaction activity, and it is recognized that the specific sizes and geometric/electronic structures of clusters are often crucial factors in determining the resulting mechanisms and reaction rates. [28][29][30][31][32][33] Also, the binding energies can fluctuate with increasing numbers of atoms, allowing clusters at a certain size to transform from a two-dimensional planar structure to a three-dimensional (3-D) structure (e.g., Pt 3 vs Pt 4 ), and occasionally leading to "magic" number species such as Al 13 − , Ag 13 − , and 12,[34][35][36] In many studies, clusters are supported on a selected substrate in order to evaluate the catalytic reactions in a practical way. The interaction between the metal clusters and support is a fundamental characteristic in heterogeneous catalysis and plays an essential role in elucidating the electronic structures, adsorption behavior, and catalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study indicated that in some rare cases the VUV ionization can lead to chemical reaction in the ionic state (Au 2 Al 2 O 3 + CH 4 → Au 2 Al 2 O 3 CH 4 , Au 2 Al 2 O 3 CH 4 + hv 118 nm → Au 2 Al 2 O 3 CH 4 + + e – , Au 2 Al 2 O 3 CH 4 + → Au 2 Al 2 O 3 H + + CH 3 ) . The generation of products such as CH 2 O (and Fe x O y –1 C 4 H 6 + ) may also be due to the VUV ionization.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, it is important to use the computational method to support the experimental observation/suggestion (reactions 2−4). Because it is very rare to observe the reaction upon single-photon VUV ionization, 70 we consider that the reactivity for most of the clusters in this study is due to the neutral state reaction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benefiting from this experimental instrument, the size-dependent reactivity of nanosized neutral manganese oxide clusters Mn 2N O 3N +x (N =2−22; x=−1, 0, 1) toward ethylene was studied [25]. Moreover, on the reaction of Au 2 Al 2 O 3 with methane, the elimination of methyl radical was observed after VUV ionization [26].…”
Section: Introductionmentioning
confidence: 99%